An Operando FTIR Spectroscopic and Kinetic Study of Carbon Monoxide Pressure Influence on Rhodium‐Catalyzed Olefin Hydroformylation. Issue 37 (31st July 2014) - Kubis, Christoph; Sawall, Mathias; Block, Axel; Neymeyr, Klaus; Ludwig, Ralf; Börner, Armin; Selent, Detlef
Abstract The influence of carbon monoxide concentration on the kinetics of the hydroformylation of 3, 3‐dimethyl‐1‐butene with a phosphite‐modified rhodium catalyst has been studied for the pressure range p(CO)=0.20–3.83 MPa. Highly resolved time‐dependent concentration profiles of the organometallic intermediates were derived from IR spectroscopic data collected in situ for the entire olefin‐conversion range. The dynamics of the catalyst and organic components are described by enzyme‐type kinetics with competitive and uncompetitive inhibition reactions involving carbon monoxide taken into account. Saturation of the alkyl–rhodium intermediates with carbon monoxide as a cosubstrate occurs between 1.5 and 2 MPa of carbon monoxide pressure, which brings about a convergence of aldehyde regioselectivity. Hydrogenolysis of the acyl intermediate is fast at 30 °C and low pressure of p(CO)=0.2 MPa, but is of minus first order with respect to the solution concentration of carbon monoxide. Resting 18‐electron hydrido and acyl complexes that correspond to early and late rate‐determining states, respectively, coexist as long as the conversion of the substrate is not complete.